2003
DOI: 10.1002/mrdd.10080
|View full text |Cite
|
Sign up to set email alerts
|

The development of reading impairment: A cognitive neuroscience model

Abstract: This review discusses recent cognitive neuroscience investigations into the biological bases of developmental dyslexia, a common disorder impacting approximately 5 to 17 percent of the population. Our aim is to summarize central findings from several lines of evidence that converge on pivotal aspects of the brain bases of developmental dyslexia. We highlight ways in which the approaches and methodologies of developmental cognitive neuroscience that are addressed in this special issue-including neuroimaging, hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(168 citation statements)
references
References 71 publications
11
154
0
3
Order By: Relevance
“…Each word was vertically flipped and its letters were segmented into simple features by using Adobe Photoshop. These segments were then rearranged to form pseudoletters, respecting the total number of characters (4) and the overall size (width × height) of the original word (24). Pseudoletters therefore contained junctions, ascending/descending features, and close-up shapes ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each word was vertically flipped and its letters were segmented into simple features by using Adobe Photoshop. These segments were then rearranged to form pseudoletters, respecting the total number of characters (4) and the overall size (width × height) of the original word (24). Pseudoletters therefore contained junctions, ascending/descending features, and close-up shapes ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…1), critically depends on the left ventral occipito-temporal cortex (2). This left hemispheric specialization is thought to arise during children's reading acquisition through reentrant mapping of sound representations in the left temporal and frontal cortices to letter representations in ipsilateral posterior areas (3)(4)(5). Even though the exact onset of this leftward specialization is not known, this process appears to take considerable time during formal reading acquisition (6)(7)(8).…”
mentioning
confidence: 99%
“…I), among other regions, in response to visual words and pseudowords as measured by fMRI [44,45] and MEG responses within the first 200 ms [14]. Such differences have not yet been associated with neuropathology in this region, but may instead reflect the absence of a specialization that accrues over the course of years of successful reading experience [55]. …”
Section: Box 3 Vwfa In Developmental Dyslexiamentioning
confidence: 99%
“…Studies of twins have suggested that phonological skills have both genetically heritable and environmentally influenced components (Fisher & DeFries, 2002;Knopnik et al, 2002), and a deficit in phonological processing is now believed to be the primary core deficit in developmental dyslexia, a reading disability in which children exhibit a difficulty in accurately or fluently reading at age-appropriate levels (L. Bradley & Bryant, 1983). This phonological impairment is reflected in dysfunction of left perisylvian cortical regions during reading tasks (McCandliss & Noble, 2003). Importantly, experimental manipulations in which reading-disabled children were exposed to both phonological skill training and explicit instruction in letter-sound correspondence rules have resulted in improved reading ability, relative to various readingdisabled control groups (L. Bradley, & Bryant, 1983;Foorman, Francis, Novy, & Liberman, 1991;Wagner & Torgesen, 1987), suggesting that phonological skill is not merely associated with reading, but actually plays a causal role in its development.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%